2021
DOI: 10.3390/children8020076
|View full text |Cite
|
Sign up to set email alerts
|

Formative Evaluation of a Home-Based Physical Activity Intervention for Adolescent Girls—The HERizon Project: A Randomised Controlled Trial

Abstract: Background. This is a formative evaluation study of the HERizon Project, a home-based multi-component physical activity (PA) intervention for adolescent girls in the UK and Ireland. Although not intended, this study coincided with the initial COVID-19 lockdown restrictions. Methods. A total of 42 female participants, aged 13 to 16 years old (mean = 14.2, SD = 1.1), were randomly allocated to: (i) the HERizon group (n = 22) or (ii) the wait-list control group (n = 20). Participants in the six-week HERizon group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 88 publications
0
12
1
Order By: Relevance
“…To obtain beneficial contributions and preventive effect of exercise and physical activities across COVID-19 (14,15), it is recommended that people should exercise at a moderate intensity for at least 150 min/week and/or walking 10000 steps/d at a rate of 64-170 steps/min for at least 10 min duration (14). (32). In contrast to result of current study, it is interesting not to improve physical activity levels of the girls (32).…”
Section: Discussionmentioning
confidence: 56%
“…To obtain beneficial contributions and preventive effect of exercise and physical activities across COVID-19 (14,15), it is recommended that people should exercise at a moderate intensity for at least 150 min/week and/or walking 10000 steps/d at a rate of 64-170 steps/min for at least 10 min duration (14). (32). In contrast to result of current study, it is interesting not to improve physical activity levels of the girls (32).…”
Section: Discussionmentioning
confidence: 56%
“…Further, it has been shown that social media can have a positive impact on health behaviours, such as improved PA and body composition [ 53 , 54 ]. Instagram was the chosen platform based on previous feedback from adolescent girls [ 7 ], and during focus groups participants confirmed that this was the most appropriate platform for the HERizon community as it was the social media they used most frequently (with Tik Tok and Discord being other recommended alternatives). Similar to Hutton and Robson [ 55 ], participant exit survey responses demonstrate moderate satisfaction and perceived usefulness of the group chat, however during focus groups and interviews it was evident that the majority of girls did not use the chat as intended.…”
Section: Discussionmentioning
confidence: 99%
“…The HERizon Project aimed to increase the PA levels of adolescent girls in the UK and Ireland. Knowledge gained from earlier formative work and a feasibility study was instrumental in the design of the current study [ 7 , 10 ]. This RCT assessed whether three intervention arms: (i) PA programme group, (ii) behaviour change support group, (iii) combined PA programme and behaviour change support group, each delivered remotely for 12 weeks, increased MVPA compared to a (iv) comparison group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations